MODEL PEMBELAJARAN PBL BERBASIS CANVA SEBAGAI PENINGKATAN MOTIVASI DAN KEAKTIFAN PESERTA DIDIK KELAS I UPT SDN 06 GRESIK - Lia Rahmawati Indrawan; Khoirul Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this study is to find out whether the use of a Canva-based PBL model can improve the motivation and activity of pupils in the learning of Indonesian language in pupils of class 1B. The method used is a class action study conducted in April-May 2024 at UPT SD Negeri 06 Gresik with subjects of 28 children. Observation and lifting are used as data collection techniques and quantitative descriptive data analysis are used for data analysis. The results of the research showed that the Canva-based PBL model helped to improve the motivation and activity of 1B class pupils at the 06 Gresik State SD UPT. In Cycle I, motivation increased by 9.8% to 64.7 and student activity also increased from an average of 58.6 to 69.9 in Cycle II, both motivation and activity increased significantly. The conclusion of this study is that the use of a Canva-based PBL model can improve the motivation and activity of students in Indonesian language lessons Class 1B UPT SD Negeri 06 Gresik.